"Nové město, nová generace, naděje pro společnost": Aneb úsilí o vybudování osady Růžičkov v Praze‑Troji (1925-1930) - Vojtko, Tibor (Lidé města, 2011)
This article concerns the Růžičkov eubiotics colony in Praque (1925-1930). The article centres on the recapitulation of the history of eugenics, social medicine, eubiotics, alternative education and the efforts to construct the Růžičkov eubiotics colony in Czechoslovakia before World War II. The central figures of the efforts were prof. Stanislav Růžička (1872-1946, author of the eubiotic theory) and Eduard Štorch (1878-1956, reform teacher).